2000
DOI: 10.1212/wnl.55.6.842
|View full text |Cite
|
Sign up to set email alerts
|

The increasing incidence and prevalence of MS in a Sardinian province

Abstract: These incidence and prevalence rates are the highest to date that have been estimated for a large community in southern Europe, and they constitute some of the highest rates in the world. Based on other surveys, these results reinforce the position of Sardinia as a higher and rising prevalence area for MS compared with other Mediterranean populations. Genetic and social-historic data strengthen the hypothesis of the environmental role and genetic factors among Sardinians in determining the notable difference i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
100
2
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(111 citation statements)
references
References 34 publications
8
100
2
1
Order By: Relevance
“…The prevalence of MS observed in the present survey of 71.2 per 100,000 population is similar to that previously reported in the same municipality [2], and together with those reported in Sardinia [7] and Enna city [4] it is one of the highest observed in the Mediterranean area. These prevalence figures confirm that Sicily is also a highrisk area for MS and further raise doubts about the accuracy of the reported latitude gradient of MS [8].…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of MS observed in the present survey of 71.2 per 100,000 population is similar to that previously reported in the same municipality [2], and together with those reported in Sardinia [7] and Enna city [4] it is one of the highest observed in the Mediterranean area. These prevalence figures confirm that Sicily is also a highrisk area for MS and further raise doubts about the accuracy of the reported latitude gradient of MS [8].…”
Section: Discussionsupporting
confidence: 92%
“…We carried out an ecological study in the Nuoro province of Sardinia, using data from a population-based case register. We found that MS affects more females than males (2.3:1), as has been previously reported [6,20], and clinical characteristics such as symptoms at onset were similar in frequency to those in other population studies [6]. The overall prevalence rate (157/100,000) is the highest value that has been estimated for any large community in Italy and southern Europe.…”
Section: Discussionsupporting
confidence: 88%
“…Italian epidemiological studies have reported prevalence rates of MS ranging from 32 to 58/100,000 inhabitants on mainland Italy [3], 153/100,000 in all of Sardinia [4], 102.6/100,000 in northwestern Sardinia [5] and 151.9/100,000 in central Sardinia [6]. A possible explanation for the worldwide geographical variation across different populations is that racial and ethnic susceptibility Montomoli et al to MS play a role that is more important than geography itself [7].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of MS reaches 151.9/100,000 in rural areas of central Sardinia [4] , and 120.2/100,000 in the central and hilly Sicilian town of Enna [1] . The most recent incidence rates range from 5.7 (Sicily) to 6.4/100,000/year (Sardinia) [1,3] .…”
Section: Introductionmentioning
confidence: 99%